2021
DOI: 10.18502/ijph.v50i10.7502
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Assessment of Cancer Patients: Prevalence and Predictive Factors of Depression and Anxiety

Abstract: Background: Patients with oncological diseases often have mental disorders in the form of comorbidity. The aim of this study was to research the association of cancer with the presence of symptoms of depression and anxiety in primary health care patients. Methods: This prospective observational study done in 2020 included adult users of health care at the Health Center Trstenik, Central Serbia, aged 19 and over, both sexes, with a diagnosis of oncological disease. A research instrument to assess depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Although the PRIME-MD has strong support in medical populations and is in the public domain, 8,35 we are aware of very few studies reporting on its use with cancer patients. [36][37][38][39][40] Our findings may support renewed interest in the PRIME-MD as a screening measure for depression in YACS and other cancer survivors. However, our results do not support the use of the PRIME-MD as a standalone screen of anxiety disorders in YACS.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Although the PRIME-MD has strong support in medical populations and is in the public domain, 8,35 we are aware of very few studies reporting on its use with cancer patients. [36][37][38][39][40] Our findings may support renewed interest in the PRIME-MD as a screening measure for depression in YACS and other cancer survivors. However, our results do not support the use of the PRIME-MD as a standalone screen of anxiety disorders in YACS.…”
Section: Discussionsupporting
confidence: 59%
“…First, our results strongly support the PRIME‐MD as a valid screening tool for depressive disorders in YACS. Although the PRIME‐MD has strong support in medical populations and is in the public domain, 8,35 we are aware of very few studies reporting on its use with cancer patients 36–40 . Our findings may support renewed interest in the PRIME‐MD as a screening measure for depression in YACS and other cancer survivors.…”
Section: Discussionmentioning
confidence: 54%
“…Incorporating mental therapies into a cancer patient's treatment plan can help control psychiatric illnesses, particularly anxiety and despair, and is recommended as a national health policy by some authors [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study with of inpatients with lung cancer in general hospitals, 43.2% of cancer patienst experienced clinically signi cant depressive symptoms (Gu et al, 2017). Also, when analysing the association between cancer and depression, Vucic et al (Vucic et al, 2021) observed that a large percentage of patients had symptoms of mild (27.2%), moderate depression (22%), and major depression (18%), and the severity of depression was higher in older adults. Our ndings reinforce that persons diagnosed with cancer present more depressive symptoms, mainly older adults.…”
Section: Discussionmentioning
confidence: 99%